Superabsorbent Hydrogel From Oil Palm Empty Fruit Bunch Cellulose And Sodium Carboxymethylcellulose - Kushairi Mohd Salleh; Sarani Zakaria; Mohd Shaiful Sajab; Sinyee Gan; Hatika Kaco (Elsevier, 2024)
Indexed by ERA